Optical flow based system design for mobile robots - Guzel, Mehmet Serdar; Bicker, Robert (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
This paper presents a new optical flow based navigation strategy, based on a multi-scale variational approach, for mobile robot navigation using a single Internet based camera as a primary sensor. Real experiments to guide a Pioneer 3-DX mobile robot in a cluttered environment are presented, and the analysis of the results allow us to validate the proposed behavior based navigation strategy Main contributions of this approach is that it proposes an alternative high performance navigation algorithm for the systems, consuming high computation time for image acquisition.